Предмет: Математика, автор: Bekoo05

lim x -> 0 (x ^ 3 - x ^ 2 + 2x)/(x ^ 2 + x)

Ответы

Автор ответа: mathkot
0

Ответ:

\boldsymbol{\boxed{  \lim_{x \to 0} \frac{x^{3} - x^{2}  + 2x}{x^{2} +x} = 2}}

Пошаговое объяснение:

\displaystyle  \lim_{x \to 0} \frac{x^{3} - x^{2}  + 2x}{x^{2} +x} =  \lim_{x \to 0} \frac{x(x^{2} - x  + 2)}{x(x +1)} =  \lim_{x \to 0} \frac{(x^{2} - x  + 2)}{(x +1)} = \frac{(0^{2} - 0  + 2)}{(0 +1)} =

= \dfrac{2}{1}=2.

Похожие вопросы
Предмет: Математика, автор: kanysh20130206